INQUIRES ABOUT ALLERGENS IN MEDICINES: EXPERIENCE FROM THE NATIONAL DRUG INFORMATION CENTER OF COSTA RICA - Bonilla-Acosta, María Laura (2023)
Currently in Costa Rica, the access to information about gluten, lactose and other allergens content in medicines is limited, which makes their safe use more difficult for people with health conditions related to these substances. This investigation aimed to promote knowledge about the presence of gluten, lactose and other allergens in medicines in Costa Rica and to describe the pharmaceutical interventions required to care for the aforementioned people, by means of the analysis of the queries related to this topic presented to the Centro Nacional de Información de Medicamentos (CIMED), which was not previously reported in our country. 182 queries regarding gluten and other allergens in medicines were included, which were presented to CIMED between February 2021 and March 2022 and whose information was registered in the center’s own database. The results show that gluten presence in the registered medicines was very low, however, 40% of the medicines for which lactose information was available were positive.  In addition, it was considered prompt to deliver pharmaceutical care interventions in many cases, amongst which health education highlighted. As a conclusion, people with health conditions related to gluten, lactose and other allergens show a clear necessity of truthful information sources regarding their content in medicines, hence it is required to include in the drug labelling normative the declaration of allergen excipients used during manufacture, and to strengthen pharmaceutical care roles, which favor, among other benefits, a safer use of their medicines. Key words: Medicines, Pharmaceutical Preparations, Allergens, Information. Source: DeCS/BIREM